Management of Life-Threatening Hemorrhage from Maxillofacial Firearm Injuries Using Foley Catheter Balloon Tamponade. Issue 4 (December 2019) - Jose, Anson; Arya, Saurabh; Nagori, Shakil Ahmed; Thukral, Himanshu
The aim of this study is to evaluate the efficacy of Foley catheter in the management of hemorrhage from penetrating maxillofacial injuries in austere environment. This retrospective cohort study evaluated all penetrating head and neck trauma caused by firearm injuries reported to a military hospital at a forward aid location during 2015-2017. Foley catheter was used in the emergency management of bleeding in 11 cases. The effectiveness of this technique in controlling hemorrhage, its indication, contraindications, and complications has been explained. Out of 26 penetrating injuries received during the time period, 11 patients underwent Foley catheter balloon tamponade for the control of hemorrhage. Ten out of 11 patients responded adequately to balloon tamponade. One patient with a bullet lodged inside the neck underwent immediate surgical exploration for its removal and repair of internal jugular vein. No neurological deficits or complications were noted in any of the patients. Foley catheter balloon tamponade is very effective in managing hemorrhage from head and neck penetrating injuries. It significantly reduces the mortality by controlling bleeding from the major vessels especially in a combat environment.